Precession-paced thermocline water temperature changes in response to upwelling conditions off southern Sumatra over the past 300, 000 years. (15th July 2018) - Wang, Xingxing; Jian, Zhimin; Lückge, Andreas; Wang, Yue; Dang, Haowen; Mohtadi, Mahyar
Abstract: Modern variations of sea surface temperature (SST) and thermocline water temperature (TWT) off southern Sumatra are responding to local upwelling conditions which are controlled by the Australian-Indonesian winter monsoon. The relationships between SST, TWT and upwelling during the past glacial-interglacial cycles are less clearly understood. In this study, SST and TWT variabilities over the past 300 kyr are reconstructed by using foraminiferal Mg/Ca-paleothermometry in sediment core SO139-74 KL off southern Sumatra (6°32.6′S, 103°50′E; 1690 m water depth). Whereas SST shows a clear glacial-interglacial cycle, TWT displays a predominant cycle at the precession band. Generally, the TWT record varies with total organic carbon content, revealing that similar to today, TWT and upwelling intensity off southern Sumatra vary in concert during the past 300 kyr. The lack of glacial-interglacial variability in the TWT suggests a limited role of glacial boundary conditions, such as changing sea level and ice volume, on the upwelling intensity in this region. The vertical gradients of upper water δ 18 O and temperature at this site also reveal precessional cyclicity. Our model simulation of air-sea interaction further supports the low TWTs during periods of enhanced upwelling and precession minimum. Highlights: First data-model approach to understand past variability of thermocline conditions in the eastern tropical Indian Ocean. The thermocline water temperature changes with a predominant cycle at the precession band. Upwelling intensity controls the upper water thermal structure off southern Sumatra over the past 300, 000 years.